The performance of highly active manganese oxide catalysts for ambient conditions carbon monoxide oxidation - Dey S.; Praveen Kumar V.V. (My University, 2025)
Ambient temperature catalytic oxidation of carbon monoxide (CO) has been widely applied in the catalytic converters for cleaning of air and lowering the automotive emissions. Carbon monoxide is a very dangerous gas present in automobile exhausts. Manganese oxide catalysts have generated much interest over the last two to three decades due to their different properties from their bulk counterparts, which opens the way for their application in various fields. Among various manganese oxides catalyst, Mn2O3 is considered to be the most favorable with respect to catalytic activity. Mn2O3 catalyst shows the best selectivity, performance and stability in manganese heterogeneous catalysis. TEM analysis shows that the manganese oxide catalyst was composed of nanorod particles with a Hausmannite structure of Mn3O4. The size and morphology of particles are major crucial factors in determining the catalytic activity of manganese oxides catalysts in structure-sensitive reactions. Catalytic oxidation of CO over manganese oxide catalysts could proceed via a Mars-van Krevelen mechanism, which involves redox process, with lattice oxygen from the catalyst surface being consumed upon reaction with pollutants and replaced by oxygen in air. The present review updates the information on various types of manganese oxide catalysts in the purification of exhaust gases. © 2020 The Author(s)